Mathematical morphology in the CIELab space - Hanbury, Allan (Image analysis and stereology, 2002)
The use of mathematical morphology in the CIE L*a*b* colour space is discussed. It is possible to impose a total order on the colour vectors in this space by using a weighting function and lexicographical order. An order analogous to one by colour saturation is suggested by making use of a weighting function based on an electrostatic potential. This weighting function assigns a lower weight to colour vectors near the colours with maximum chroma, and higher weights to colour vectors near the lightness axis. The use of morphological operators with the colour vector order imposed by this function is demonstrated. Finally, a top-hat operator making use of the Euclidean colour distance in the L*a*b* space is introduced.
Keywords: Barva; Color; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Modeli teoretski; Models, Theoretical; stereologija; analiza slik; morfologija; modeli